Improving Academic Writing Skills through Contextual Teaching Learning for Students of Bosowa University Makassar - Syahriah Madjid; Emzir Emzir; Sabarti Akhadiah (JETL (Journal of Education, Teaching and Learning), 2017)
The purpose of this research is for helping students to improve their academic writing skills by changing the existing strategies which were considered ineffective at solving this kind of problem. This research was about how to improve student’s academic writing skills through contextual teaching and learning. The clientele of this research was the students of Civil Engineering Department of Bosowa University of Makassar. To gain the final result in this research there are three periods were needed. The result for the first period is only 26.67% or only 8 from 30 students could pass the standard qualifying. The students which passed the standard qualifying becomes 80% from 30 students in next period and in the final period the result was already succeeded, all of the students could pass the standard qualifying. Those experiments prove that this research showed that contextual teaching and learning effects can be used in helping students improve their academic writing skills. This research recommends the lecturer to conduct intensive training in the process of planning to write, the evaluation of sources of references, and the development of writing based on academic writing strategy.